REVISED BCIA PROPOSAL - DYER,DM (Tufts Archival Research Center, 2007)
Marginalia; Memo restating a Business Council on Indoor Air (BCIA) proposal. Expresses concern over workplace smoking, indoor air quality, and a general education and image problem for the tobacco industry at all levels. Identifies need to create a business coalition adressing indoor air without any contact with the tobacco industry. Provides overview of the plan and steps for its implementation. Estimates costs.